Integration of nanomaterials in halal food production: safety, regulatory, and ethical perspectives - Elgharbawy, Amal A.M.; Azmi, Nor Azrini Nadiha; Mohd Noor, Najihah; Syed Putra, Sharifah Shahira; Yuhan, Avicenna (Academic Press, Elsevier, 2026)
Nowadays, the modern world is facing increasingly complex challenges related to food safety and security. With the growing world population, ensuring the availability of safe and nutritious food has become a top priority. Therefore, this chapter explores how nanotechnology, such as nanomaterials, can help address these critical issues. Nanomaterials, with their unique properties, provide innovative solutions to enhance food safety by enabling real-time pathogen detection, intelligent packaging, and contaminant removal. They also improve food security by optimizing nutrient delivery, extending shelf life, and promoting sustainable agricultural practices. This chapter discussed a comprehensive overview of the types of nanomaterials, their synthesis and characterization methods, and their diverse applications in the food industry. The regulatory frameworks for using nanomaterials in food, covering global guidelines and specific regulations in Malaysia, were also explored. Hence, it serves as an invaluable resource in the evolving discussion on nanotechnology's role in enhancing food safety and security.